ANALISIS KESALAHAN INTONASI DAROU PADA MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA JEPANG UNIVERSITAS RIAU - Muhammad Nasirudin; Arza Aibonotika; Adisthi Martha Yohani (Jurnal Pendidikan Bahasa Jepang Undiksha, 2022)
Intonation is one of the most important elements that affect the meaning of some sentences. Specifically, Darou Intonation, which is the meaning of the word will change if the intonation is wrong. The goal of this study is to find how a miss pronunciation of the intonation of the Japanese word Darou. this study is using a descriptive qualitative method. Also, an instrument used in this study is using the speaking test. The participants in this study are 34 people from the 2018 class of the Japanese language education program at Riau University. The final result of this study indicates that half of the students that participated in the speaking test were still wrong on the test.